Two cut-free modal sequent calculi - Arsov, Andrei (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1995)
In this paper the modal approach to concept languages is considered. Two sequent-style calculi for the modal systems $\mathcal{AL}$ and $\mathcal{ALN}$ are introduced and the cut-elimination property is proved.